Menavigasi Hibriditas: Tantangan dan Peluang Kolaborasi Publik-Privat dalam Transformasi Layanan Kesehatan Indonesia - Rulinawaty, Rulinawaty; Samboteng, Lukman; Andriyansah, Andriyansah; Kasmad, M. Rachmat; Alwi, Alwi; Basit, Mutmainnah (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
Hybrid organizations that combine elements of the public and private sectors are growing in healthcare in Indonesia, but their impact and management are still debated. This study aims to identify and analyze the dimensions of hybridity and its impact in operational practices. A qualitative case study method was used with a multidimensional analysis of three hybrid healthcare organizations in Indonesia, involving in-depth interviews, observation, and document analysis. The results showed that organizational hybridity includes variations in legal form, ownership, funding, activities, strategic orientation, organizational culture, and governance, which simultaneously create positive impacts such as innovation, efficiency, and improved service quality, as well as negative effects such as internal value conflicts, unfair cross-subsidies, and public accountability challenges. This study confirms the importance of strategic management and pragmatic approaches in understanding and managing hybrid organizations, and makes significant theoretical and practical contributions to health sector policy development. Further research is recommended to explore optimal governance strategies in the context of other hybrid organizations in Indonesia.